S140 Interim results from a prospective study of tablet and web- based audiometry to detect ototoxicity in adults with cystic fibrosis. (December 2018) - Vijayasingam, A; Shah, A; Simmonds, NJ; Elston, C; Frost, E; Wilkins, J; Picinali, L; Premachandra, P; Gillen, L; Morris-Rosendahl, D; Ni, M
Abstract : Introduction: Individuals with Cystic Fibrosis (CF) often receive frequent, prolonged anti-infective therapy including aminoglycosides which result in ototoxicity. There are, however, no current national or international screening recommendations. Although high-frequency audiometry has increased sensitivity for early detection of drug-induced hearing loss, formal audiometry is costly and requires further outpatient visits. We analyse the validity of an interactive Apple-iPad app-based high-frequency audiometer ( Shoebox MD ) that can be used by non-audiologists to test hearing in an outpatient setting to screen for ototoxicity in an adult CF population. Methods: Adults with CF at the Royal Brompton and Harefield or Kings College Hospital NHS Foundation Trusts are being recruited over an 8 month period. Hearing was analysed with an iPad app in an outpatient setting by non-audiologists followed by formal audiometry. A threshold of ≥25 dB hearing loss at one or more audiometric frequencies was considered to be outside the normal hearing range. Correlation analysis was used to determine reliability of iPad compared to formal audiometry at individual frequencies. Sensitivity and specificities were analysed to determine efficacy of iPad audiometry as a screening tool. Demographics are currently being collected to determine risk factors for hearing loss development and genomic sequencing performed to analyse mitochondrial mutations associated with aminoglycoside related hearing loss. Results: Interim results of the first 28 participants show an overall prevalence of hearing loss in our cohort of 39%. Significant positive correlation between the iPad interactive and formal audiometry was seen at high frequencies (see figure 1) but relatively poor correlation at low frequencies where hearing loss is however uncommon in our cohort. iPad interactive audiometry showed a sensitivity of 91%, specificity of 82% and negative predictive value of 93% to identify adults with hearing loss, highlighting its potential use for ototoxicity screening in this population. Conclusion: We present interim results highlighting for the first time, the use of novel app-based audiometry as a screening tool for aminoglycoside induced hearing loss in adult CF with potential application in other chronic lung disease cohorts. Full results will be presented at the conference.